ANALISIS PEMBIAYAAN PEREMAJAAN KEBUN KELAPA SAWIT RAKYAT KOPERMAS TUAH MEUSAPAT MELALUI DANA SKIM HIBAH BPDP SAWIT INDONESIA DI KABUPATEN ACEH BARAT - Aswin Nasution (Universitas Teuku Umar, 2017)
The Indonesian government established PP. Number 24 Year 2015 about Plantation Funds Funding and Prepres No. 61 Year 2015 about the Collection and Use its funds from the collection of export of CPO and its derivatives. The collection and management funds conducted by Indonesian Oil Palm BPDP. Results of research conducted that Tuah Meusapat Kopermas that will do the rejuvenation of oil palm plantation using BPDP oil palm grant shows that rejuvenation farmers oil palm plantation 400 hectare are use oil palm BPDP Rp. 25,000,000,- and sharing of farmers funds Rp. 35,000,000, - per hectare with total rejuvenation fund of Rp. 24,000,000,000, - per 400 hectare. Three alternative funding schemes show : 1) Skim-I 100% farmer’s funds Rp. , - per hectare, requirement of Rp. 60,000,000, - per hectare; 2) Skim-II 50% farmer's fund Rp. 17,500,000, - and 50% bank credit Rp. 17,500,000, - interest annuity bank during construction 12% Rp. 6,917,656, -, l requirement Rp. 66,917,656, - per hectare; and 3) Skim-III farmers fund 100% of banking credit Rp. 35,000,000, - interest annuity bank during construction 12% Rp. 13,835,311, -,the total requirement of Rp. 73,835,311, - per hectare. The three funding schemes have equal opportunities to be implemented, but depends on the financial capacity of farmers. The baseb of project feasibility on NPV, IRR,B / C Ratio, Payback Period and BEP the products creterias the three schemes are feasible.